Microtubule Protein βIII-Tubulin: Structure, Expression and Functions in Normal and Tumor Cells - I. A. Mamichev; T. A. Bogush; E. A. Bogush; N. S. Terentyeva; V. Y. Kirsanov; M. M. Davydov (Антибиотики и Химиотерапия)
The present review contains data on microtubular protein ßIII-tubulin (TUBB3): its structure, functions, role in tumor progression, expression in normal cells and in neural and epithelial tumors of different origins. Basic working principles of microtubular system and links between TUBB3 and related β-tubulins are also briefly reviewed. We analyzed the clinical potential of TUBB3 as prognostic marker of tumor aggressiveness and drug-resistance and suggested that locally disseminated tumor cells might be found by comparison of TUBB3 expression in normal and tumor tissue of each patient. Finally, we conclude that screening for TUBB3 and other tumor markers in morphologically normal tissue adjacent to the tumor is essential for accurate diagnostics.